A Cross-Country Analysis on Capital Flows Cycle: Stylized Facts and Regional Synchronization - Yang, Yang; Yang, Haizhen; Zhang, Mengting (Asian Economic and Financial Review, 2021)
Capital flows often behave in waves, have strong cyclical profiles and show greater volatility, especially before and after a financial crisis. This study analyzed the cyclical characteristics of capital flows from the perspectives of duration, amplitude and speed. First, by identifying the capital flows cycles of 60 representative economies from Q1 1980 to Q1 2020 using the Bry and Boschan Quarterly (BBQ) algorithm, we found that small economies generally have higher amplitude and speed of net capital flows compared with large economies. The duration of the capital flows cycle in most regions had significantly shortened after the global financial crisis in 2008. Further, we investigated the regional synchronization of capital flows cycles, and the results show that the degree of regional synchronization of capital flows cycles within advanced economies is high, while it is relatively low within emerging and developing economies. In addition, the capital flows cycle between advanced Asian economies and any region of emerging and developing economies is highly synchronized. The study provides insights for understanding the relationship between financial crises and the volatility of capital flows.